The Interest of the Convert: Marius Theodorian-Carada and the Romanian Greek-Catholic Church in the First Decades of the 20ᵗʰ Century - TURCU, Lucian (Studia Universitatis Babeș-Bolyai Historia, 2024)
The present study aims to present the situation of the Greek-Catholic community in Bucharest in the first decades of the 20th Century, starting from the reports that Marius Theodorian-Carada sent to the Holy See at that time. As a convert to Greek Catholicism in 1908, Theodorian-Carada showed an increased interest in the situation of the Greek Catholic believers in Bucharest during the interwar period, more precisely after the parish of Saint Basil the Great had been placed under the authority of the Greek-Catholic Archdiocese of Blaj. The present paper covers the intellectual profile of the convert, his continuous activism for the cause of the union of the Orthodox Church in Romania with the Catholic Church and, above all, the solutions that Theodorian-Carada proposed in response to the most urgent problems that the Romanian Greek Catholic Church was facing at that time. Last but not least, our study sheds light, based on archival documents, on the perspective that the Nunciature from Bucharest and the Greek-Catholic hierarchy had on the issues raised. Rezumat: Studiul de faţă are în vedere prezentarea situaţiei comunităţii greco-catolice din Bucureşti în primele decenii ale secolului al XX-lea pornind de la rapoartele pe care Marius Theodorian-Carada le-a trimis în acele vremuri Sfântului Scaun. În calitate de convertit la greco-catolicism în 1908, Theodorian-Carada a manifestat un interes sporit faţă de situaţia credincioşilor greco-catolici din Bucureşti în perioada interbelică, mai exact după ce parohia Sfântul Vasile cel Mare de acolo a fost pusă sub autoritatea arhidiecezei greco-catolice de Blaj. S-a avut în vedere profilul intelectual al convertitului, activismul său susţinut pentru cauza unirii Bisericii ortodoxe din România cu Biserica catolică şi, mai ales, soluţiile pe care Theodorian-Carada le-a formulat la cele mai stringente probleme cu care se confrunta în acele timpuri Biserica greco-catolică românească. Nu în ultimul rând, studiul nostru pune în lumină, pe baza documentelor de arhivă, perspectiva pe care Nunţiatura de la Bucureşti şi ierarhia greco-catolică au avut-o asupra problemelor reclamate. Cuvinte-cheie: Parohia greco-catolică Sfântul Vasile din Bucureşti, unirea Bisericilor, limba liturgică, presă religioasă, greco-catolici în Vechiul Regat român Article: history; Received: 20.11.2023; Revised: 19.12.2023 Accepted: 28.12.2023; Available online: 30.01.2024